Timber clinker as partial replacement of 20mm natural coarse aggregate in concrete - Loo, Khee Hui (2015)
This dissertation presents the results of an experimental investigation carried out to evaluate effects of partially replacing coarse aggregates with that of timber clinker on the concrete strength properties. A series of tests were conducted to determine the physical properties of Timber Clinker Aggregate (TCA), namely aggregate density, X-Ray Fluorescence (XRF) test, Aggregate Crushing Value (ACV), Aggregate Impact Value (AIV), slump and properties of Timber Clinker Aggregate Concrete (TCAC) in terms of density and compressive strength. Four (4) series of concrete mix with targeted compressive strength of 30 MPa is produced with partial replacement ratio of 0%, 10%, 20% and 30% of 20mm sieve size TCA to the natural course aggregate and incorporating superplasticizer, known as Supracoat SP800. A total nos. of forty (40) concrete cube specimens (150mm x 150mm x 150mm) were casted and tested for 7 and 28 day’s strength characteristic. The study indicated that with the increase of replacement ratio, the compressive strength gradually decreases. However, C10 is managed to achieve the strength of 32.27 MPa while C20 still acceptable for structural use, with strength of 28.40 MPa. Workability decrease as the replacement ratio increase, which indicating TCA is high in water adsorption. A close study on the physical properties reveals that TCA is lower in mechanical strength that might contribute to the lower compressive strength of TCAC. Based on this study, TCA is still acceptable for the structural uses purposes with optimum replacement ratio of 20%.